Flexor Tendon Rupture After Distal Radius Malunion Associated With Electromyographic Abnormalities: A Case Report. Issue 2 (2020) - Lalchandani, Gopal R.; Chan, Alvin; Nagao, Masato; Immerman, Igor
Abstract : Case: A 63-year-old woman with a history of a malunited distal radius fracture presented with left hand pain and inability to flex her thumb, index, and middle fingers. Anterior interosseous neuropathy was suggested because of abnormal electromyography findings. However, magnetic resonance imaging later revealed flexor tendon ruptures. A distal radius corrective osteotomy with autograft and volar fixation was performed with tendon transfers and carpal tunnel release. Conclusions: Attritional flexor tendon rupture after a nonoperatively managed distal radius fracture is rare but remains an important differential diagnosis in patients with signs and symptoms of anterior interosseous nerve paralysis.